Clinical and laboratory investigation on the recurrence of the umbilical hernia after herniorrhaphy in bovine calves: Recurrence of umbilical hernia in calves (Journal of the Bangladesh Agricultural University, 2018)
This study was performed to investigate the recurrence of the umbilical hernia in bovine calves at Veterinary Teaching Hospital (VTH), Bangladesh Agricultural University, Mymensingh. A total of 34 animals were admitted to VTH diagnosed to have the umbilical hernia, among them 13 were recurrent cases. The diagnosis of umbilical hernia was based on the disease history, clinical signs, palpation, needle exploration, and auscultation. The risk factors like age, sex, breed, body weight, the season of affection, size of the hernial ring, suture materials, error in suture patterns and involvement of infections in the recurrence were considered.  Infected samples were collected from recurrent patients with infected umbilicus region, and subjected to bacteriological analysis. We found the recurrence percentage was higher in the crossbred (44%) than that in the indigenous (22.22%) calves. It was also observed that recurrence percentage was higher in male (42.11%) than those in female (33.33%) patients. The recurrence percentage was also higher in calves aged below three months (40.74%) than the calves of above three months (28.57%). It was found that recurrence percentage was most frequent in summer (46.15%) and the least in the winter (30%). Among 13 recurrent bovine calves after herniorrhaphy, three calves returned to VTH with umbilical abscess, six calves recurred due to non-infectious causes like failure of suture materials, errors in suture pattern or management fault and 4 calves recurred with both umbilical abscess and non-infectious causes. From this study, it may be concluded that synthetic absorbable suture materials with secured suture pattern and good postoperative management may help in reducing the recurrence of an umbilical hernia.J. Bangladesh Agril. Univ. 16(3): 464–470, December 2018